Biological control of cyanobacterial bloom by leaf biomass - Zainuddin, Zarina; Lalung, Japareng; Yusof, Tengku Nadiah; Rafatullah, Mohd; Ismail, Norli (2021)
Cyanobacteria are able to grow rapidly when induced by suitable conditions and form blooms. These cyanobacterial blooms can lead to wide ranges of water quality problems which include depletion of dissolved oxygen and subsequent fish kills and unsafe drinking water. To a greater extent, cyanobacteria can severely degrade aquatic habitats, decrease the utilisation of water bod- ies as potable water supply, limit recreational activities and reduce in-lake fisheries. Previous researches conducted showed that plant leaves released anti-cyanobacterial compounds. Hence this study investigated the abilities of 15 terrestrial wild plant leaves leachates from Penang, Malaysia to inhibit the growth of 8 isolated cyanobacteria. The results showed that most leaves effectively controlled all cyanobacterial growth but at different rates, depending on the species of cyanobacteria and the plant leaves used. The outcomes suggest that the wild plant terrestrial leaves released effective anti-cyanobacterial substances, giving new insight to terrestrial leaves as natural biological controls of cyanobacterial bloom.